PENGEMBANGAN MEDIA KARTU KWARTET TEMA 9 SUBTEMA 1 DAN SUBTEMA 2 KELAS V SEKOLAH DASAR SWASTA - Fadli Surahman; Haidir; Dirneti; Erika; Eka Lenggang Dianasari (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This writing problem is lack of learning media used in schools makes students less active in learning, thus causing children not to pay attention to the teacher explaining and often disturbing friends next to them. This study aims to determine the feasibility of the quartet card media for Class V students. This type of research is development research with the Borg and Gall model, there are ten steps of development research, the trial subjects consisted of 2 material experts, design experts, 2 class V teachers at SDS 018 Plus Avicenna Indonesia, 4 grade V SDS 018 students. Plus Avicenna Indonesia for initialfield trials, 8 grade V SDS 018 Plus Avicenna Indonesia students for small group trials, 25 grade V students at SDS 018 Plus Avicenna Indonesia for large group trials. The results showed that: (1) validation of material experts based on eligibility according to the subcomponent as a whole was in the criteria of